3D Printed Maxillofacial Trauma Plates as a Valuable Alternative to Conventional Miniplates: A Case Report - chakravarthy, Dr.chitra; gawade, kiran; Mathpati, Santosh Kumar; G., Neelesh; V., Manjula (International Journal of Innovative Research in Medical Science, 2024)
The principles in treating complex mandibular fractures have changed recently, although the objective of re-establishing the occlusion and masticatory function remains the same. Technological upgrades like 3D-printed customized plates and implants have replaced traditional stock plates by achieving safe and desirable anatomical and functional restoration with reduced operative time. In this case report, we aimed to design and employ customized 3D-printed titanium plates for mandibular reconstruction in a case with complex mandibular fracture. A preoperative CT scan of the patient was taken to evaluate the displacement between the fractured segments. Virtual surgical planning was done, and 3D-printed titanium plates were simulated, customized, fabricated, and placed following Champy’s line of osteosynthesis for the approximation of fractured segments and to guide the occlusion during surgery. A postoperative CT scan was taken and overlapped with the preoperative virtual surgical plan scan to assess the interfragmentary gap after reduction and the amount of deviation. The result achieved was satisfactory, with no complications reported. The use of customized 3D printed-Ti plates in the treatment of mandibular fracture had better accuracy and adaptability to the bone, avoided the need for plate bending, improved operator efficiency, and resulted in fracture reduction with satisfactory outcomes.